Pengaruh Hard Skill Dan Soft Skill Terhadap Kinerja Karyawan Pada Sentra Industri Boneka Di Sukamulya Bandung. - Fhalina Lisdiana Hardi (Jurnal Riset Mahasiswa, 2020)
Hard Skill is the main factor for Employee Performance, several studies show that Hard Skill and Soft Skill can improve Employee Performance. This study aims to determine how much the influence of Hard Skill and Soft Skill on Employee Performance at the Center for Doll Industry in Sukamulya Bandung both partially and simultaneously. The research method used was descriptive and verification with a sample of 117 employees. Data collection techniques used were interviews, observations, questionnaires. The data analysis method used is multiple linear regression analysis, multiple correlation and coefficient of determination. The results showed that Hard Skill, Soft Skill and Employee Performance variables were in the Poor category. Quantitative results show that Hard Skill and Soft Skill have an influence on Employee Performance by 65.5%. Partially, the Hard Skill has a greater effect on Employee Performance, which is equal to (50.5%), while the Soft Skill effect on Employee Performance is only (15%).